PSYCHOLOGICAL FEATURES OF INTERACTION OF HIGH SCHOOL STUDENTS, TUTORED AT HOME - Shilova, T.A.; Kostereva, L.I. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ psikhologii͡a︡ i pedagogika, 2017)
The article deals with the data of theoretical and empirical research of psychological features of interaction of high school students tutored at home. The empirical study involved 80 high school students aged 15-17 years living in Moscow: 40 students studying in a secondary school, 40 subjects tutored at home, using psychodiagnostic methods: methods of “Self-attitude research by V.V. Stolin and S.R. Panteleeva”; “Evaluation of the level of sociability” method (V.F. Ryakhovskiy); diagnostics methods for communication attitude (V.V. Boiko); the method of “Personal Differential”. In the course of the study we found pronounced differences in the psychological features of interaction in high school students studying in a secondary school and tutored at home. The high school students tutored at home showed low communicative interaction skills, unlike their peers who are studying in a secondary school. Also a difference in the manifestation of the specific components of the self-attitude: inwardness, self-confidence, self-affection, internal conflict, self-blame was found. The results of the study confirm the proposed hypothesis put forward that the frequent and prolonged isolation from society leads to disruption of communication skills and can negatively affect personality development. The practical aspect of the problem under study allows defining and developing a program of psychological support for pupils tutored at home, for the development of communicative interaction skills and personal growth.